2015
DOI: 10.1007/s00262-015-1702-8
|View full text |Cite
|
Sign up to set email alerts
|

6-Thioguanine-loaded polymeric micelles deplete myeloid-derived suppressor cells and enhance the efficacy of T cell immunotherapy in tumor-bearing mice

Abstract: Myeloid-derived suppressor cells (MDSCs) are a heterogeneous population of immature myeloid cells that suppress effector T cell responses and can reduce the efficacy of cancer immunotherapies. We previously showed that ultra-small polymer nanoparticles efficiently drain to the lymphatics after intradermal injection and target antigen-presenting cells, including Ly6chi Ly6g− monocytic MDSCs (Mo-MDSCs), in skin-draining lymph nodes (LNs) and spleen. Here, we developed ultra-small polymer micelles loaded with 6-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 56 publications
0
33
0
Order By: Relevance
“…This example offers an effective way to prolong drug function in the tumor environment by using a nanodelivery approach. Other recent examples include using poly (ethyleneimine) nanoparticles for the delivery of antiPD-1 siRNA (Teo et al, 2015), branched polyethyleneimine-superparamagnetic iron oxide nanoparticles for the enhancement of Th1 cell polarization of DCs (Hoang et al, 2015), 6-thioguanine-loaded polymeric micelles for the depletion of MDSCs (Jeanbart et al, 2015), and a CD4-targeted, oil-in-water emulsion for the co-delivery of IL-2 and TGF-β (McHugh et al, 2015). …”
Section: Achievementsmentioning
confidence: 99%
“…This example offers an effective way to prolong drug function in the tumor environment by using a nanodelivery approach. Other recent examples include using poly (ethyleneimine) nanoparticles for the delivery of antiPD-1 siRNA (Teo et al, 2015), branched polyethyleneimine-superparamagnetic iron oxide nanoparticles for the enhancement of Th1 cell polarization of DCs (Hoang et al, 2015), 6-thioguanine-loaded polymeric micelles for the depletion of MDSCs (Jeanbart et al, 2015), and a CD4-targeted, oil-in-water emulsion for the co-delivery of IL-2 and TGF-β (McHugh et al, 2015). …”
Section: Achievementsmentioning
confidence: 99%
“…They found that MC‐TG NPs more effectively decreased the numbers of circulating monocytic and granulocytic MDSCs than equal doses of free TG. Overall, this MDSC‐depleting strategy enhanced cancer immunotherapy in the B16‐F10 melanoma model …”
Section: Nps’ Structures For Cancer Immunotherapymentioning
confidence: 92%
“…Poly(propylene sulfide)–PEG micelles were developed to encapsulate 6‐thioguanine for the depletion of MDSCs in EG7 and B16 tumor‐bearing mice, and they enhanced the efficacy of adoptive T‐cell therapy . The sub‐30 nm polymeric micelles allowed the efficient delivery of 6‐thioguanine to the lymphatic system to deplete monocytic MDSCs in the TME and spleen and granulocytic MDSCs in the tumor‐draining lymph nodes.…”
Section: Nanoengineering Immune Niches To Enhance Cancer Immunotherapymentioning
confidence: 99%